Magnetic Properties of Yamato-73-04 and Yamato-73-07 Meteorites - Nagata, Takesi; Sugiura, Naoji; Schwerer, F.C. (1976)
P(論文) Two Yamato meteorites collected in 1973 in Antarcica, Yamato-73-04 and Yamato-73-07, may be identified to an olivine-bronzite chondrite and a hypersthene achondrite respectively from their petrographic and chemical compositions. Magnetic analyses indicate that native irons in Yamato-73-04 chondrite comprise 2.6wt% of 7wt% Ni kamacite and 4.3wt% of 13wt% Ni kamacite, and that Yamato-73-07 achondrite contains 0.24wt% of Fe^0 with small amounts of Ni and Co and less than 0.02wt% of 60wt% Ni taenite or Fe_<3-x>Cr_xO_4. The natural remanent magnetization, NRM, of Yamato-73-07 achondrite can be distinctly separated into the original NRM of the undisturbed interior of 6.3×10^<-6> emu/gm in intensity and the secondary NRM of the surface skin fusion crust of about 0.5mm in thickness. The secondary NRM is attributable to the thermoremanent magnetization acquired in a magnetic field of 0.44 Oe-probably the geomagnetic field. departmental bulletin paper